PENGUATAN KARAKTER RAHMATAN LIL ‘ALAMIN PADA SISWA MTS MELALUI KETELADANAN GURU PAI - Sahal Tamrin; Zainul Hakim; Sunardi; Zulfikri; M Renaldy Fadilah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
Strengthening rahmatan lil ‘alamin character among MTs students is essential because learners at the early adolescent stage require concrete role models to understand and practice Islamic values in a polite, tolerant, caring, and responsible manner. This study aims to describe the strengthening of rahmatan lil ‘alamin character among students at MTs Al Hasanah Palabuhanratu Sukabumi through the exemplary conduct of Islamic Religious Education teachers. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the exemplary conduct of Islamic Religious Education teachers is reflected in polite communication, discipline, fairness, care, educative correction, and active involvement in religious activities at the madrasah. The values strengthened include politeness, care, tolerance, peacefulness, responsibility, and discipline. In conclusion, the exemplary conduct of Islamic Religious Education teachers serves as an effective medium for internalizing rahmatan lil ‘alamin character because students learn through observation, imitation, and habituation. The implications of this study highlight the importance of strengthening the madrasah’s religious culture, maintaining consistent teacher role modeling, and enhancing collaboration between the madrasah and families in fostering students’ character.